OVERLAID CHISEL BLADE LOCATION RELATIVE TO DIRECTION OF PLOWING UNIT MOVEMENT - I. V. Liskin; D. A. Mironov; R. K. Kurbanov (Сельскохозяйственные машины и технологии)
An overlaid chisel of a compound ploughshare is the most loaded part which is important for operability of a ploughshare and  implementation of agrotechnical requirements for plowing depth.  Chisels of ploughshares are made by methods of stamping and  blanking with use of gas, laser or plasma machines. Parts from a  rolled strip are the most wearresisting. Сhisels with big difference on plowing depth between extreme points of an edge are the best for  heavy soils cultivation because of partial destruction of the soil  bottom layer. When light and medium soils plowing the difference of  depth between extreme points of an edge of a chisel is reduced for  decrease in traction resistance of a ploughshare. On light soils with  the hardness up to 2.7 MPa the plows equipped with ploughshares  with the chisels having the minimum difference on depth between extreme points of an edge have the minimum traction resistance. When difference raises up to 30 mm traction resistance increases on  average for 5.5 percent. This dependence is close to linear if  difference of depth varies from 10 to 30 mm. The overlaid chisels are recommended for ploughshares at cultivation of light and heavy soils by plows of general purpose. The angle between a chisel edge and a  furrow wall should to be direct, and the difference of depth between extreme points on the line crossing an edge and sides of the chisel should be in an interval of 15-20 mm.